2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30931
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Student Perceptions of Their Abilities on the ABET Student Outcomes to Succeed During the First-Year Engineering Program

Abstract: Delivering significant results in pivotal roles such as Sr. Consultant to high-profile clients, Sr. Project Manager directing teams, and Executive Leader of initiatives and programs that boost organizational effectiveness and optimize operations have been hallmarks of Dr. Wickliff's career spanning more than 24 years with leaders in the oil & gas and semiconductor industries. As an expert in the areas of Executive Leadership and Team Development, Strategy Design & Execution, Supply Chain Optimization, Change M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Moreover, many introductory engineering courses worldwide have a component of programming or computational thinking. A preliminary study of enculturation to the engineering profession found that computational thinking was deemed a critical area of development at the early stages of instruction (Mendoza Diaz et al, 2018, 2019Richard et al, 2016;Wickliff et al, 2018).…”
Section: Computational Thinking Diagnostics For First-year Engineering Students: Year Imentioning
confidence: 99%
“…Moreover, many introductory engineering courses worldwide have a component of programming or computational thinking. A preliminary study of enculturation to the engineering profession found that computational thinking was deemed a critical area of development at the early stages of instruction (Mendoza Diaz et al, 2018, 2019Richard et al, 2016;Wickliff et al, 2018).…”
Section: Computational Thinking Diagnostics For First-year Engineering Students: Year Imentioning
confidence: 99%